Hubungan Pengetahuan Akseptor Kb terhadap Pemakaian Kontrasepsi Implan di Kota Palembang Tahun 2017 - Yusnilasari, Yusnilasari; Ariani, Debby Utami Siska (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Data of Health Office of Palembang City Year 2014, from 16 sub districts in Palembang city, there are 4 districts which proportion of new KB 0% implant participants, ie District Ilir Barat II, Plaju, Kalidoni and Sematang Borang where from 4 Subdistricts have 6 Puskesmas with each of the proportion of participants of new KB Implants also 0% Sie Makrayu Health Center, Plaju, Bukit Sangkal, Kalidoni, Sei Selincah and Sematang Borang. This study aims to know the relation of knowledge of acceptor of KB to implant contraception usage in Palembang city year 2017. This research design is analytic survey with Cross sectional approach. The population used by the researcher is the family planning acceptors who are in the working area of ​​Makrayu Health Center, Plaju, Sarang Hill, Kalidoni, Sei Selincah and Sematang Borang City of Palembang in 2017 and the sample number is 30 respondents. Sampling technique using Simple Random Sampling approach. Bivariate analysis using chi square statistical test (α = 0,05). The instrument used for data collection is a questionnaire conducted at 6 health centers in Palembang city. The results obtained p value 0.002 <α (0.05), it shows that there is a relationship between the knowledge of respondents with the use of contraceptive implants in Palembang City Year 2017. Test results also obtained OR = 3,143. The conclusion of this research is that there is a correlation between the knowledge of respondents with the use of contraceptive implants in Palembang City in 2017. It is expected to build positive information about KB Implant by involving the role of health cadres through extension activities and dissemination of information about the success of Implant use.